The Electrophysiological Determinants of Corticospinal Motor Neuron Vulnerability in ALS - Jara, Javier H.; Sheets, Patrick L.; Nigro, Maximiliano José; Perić, Mina; Brooks, Carolyn; Heller, Daniel B.; Martina, Marco; Andjus, Pavle R.; Ozdinler, P. Hande (Frontiers in Molecular Neuroscience, 2020)
Brain is complex and heterogeneous. Even though numerous independent studies indicate cortical hyperexcitability as a potential contributor to amyotrophic lateral sclerosis (ALS) pathology, the mechanisms that are responsible for upper motor neuron (UMN) vulnerability remain elusive. In an effort to reveal both intrinsic and extrinsic factors that contribute to corticospinal motor neuron (CSMN, a.k.a UMN in mice) vulnerability, we investigated the motor cortex of hSOD1G93A mice at P30 (postnatal day 30), ¬a presymptomatic time point. Glutamate uncaging by laser scanning photostimulation revealed altered dynamics especially within the inhibitory circuitry and more specifically in L2/3 of the cortex, whereas the excitatory microcircuits were unchanged. Observed microcircuitry changes were specific to CSMN in the motor column. Electrophysiological evaluation of the intrinsic properties in response to the microcircuit changes, as well as the exon microarray expression profiles of CSMN isolated from hSOD1G93A and healthy mice at P30 revealed the presence of a very dynamic set of events, ultimately directed to establish, maintain and retain the balance at this early stage. In addition, the expression profile of key voltage gated potassium and sodium channel subunits as well as of the inhibitory GABA receptor subunits and modulatory proteins began to suggest the challenges CSMN face at this early stage. Since neurodegeneration is initiated when neurons can no longer maintain balance, the complex cellular events that occur at this critical time point help reveal how CSMN try cope with challenges of disease manifestation. This information is critically important for proper modulation of upper motor neurons and for developing effective treatment strategies in the near future.